Hello, Dolly! [compact disc] : the new Broadway cast recording - Herman, Jerry, 1931-2019- (Masterworks Broadway, 2017)
Bette Midler returns to Broadway in the starring role in one of the year's hottest tickets. Joining her in this revival are David Hyde Pierce, Gavin Creed, and Kate Baldwin.